Transforming Intermediation of Islamic Financial Institutions through Sharia Principles - Yulianti Ika Susilawati; Rudi; Rony Iskandar (Research Horizon, 2025)
The transformation of the intermediation function of Islamic Financial Institutions (IFIs) is a strategic necessity to meet the demand for a fair, transparent, and sustainable financial system. Despite rapid growth, the Financing to Deposit Ratio (FDR) of IFIs still lags behind the Loan to Deposit Ratio (LDR) of conventional banks, indicating suboptimal intermediation. This study aims to analyze the effectiveness of the intermediation function of IFIs through the integration of sharia principles such as justice, partnership, and the prohibition of usury. Using a qualitative descriptive approach, data were gathered through literature studies, documentation, and analysis. The results show that Islamic business ethics and the values of maqashid sharia strengthen the intermediation role of IFIs, positioning them not only as financial intermediaries but also as agents of social change. However, a significant challenge is the limited effectiveness of the Sharia Supervisory Board (SSB), caused by weak regulations, limited operational reach, and low involvement in product innovation. The study underscores the need to enhance the SSB’s role and regulatory synergy to improve IFIs governance. The findings contribute both theoretically, by proposing sharia-based FDR effectiveness, and practically, by offering insights for policymakers to optimize IFIs' role in inclusive and sharia-compliant economic development.